Hierarchical Task Analysis Reimagined as a Planning Tool for Surgery During Exploration Space Flight. (October 2022) - Miller, Karen Hughes; Sutton, Erica; Pantalos, George
Background: Preparation for exploration class space flight requires planning to support human life in many circumstances including healthcare emergencies such as the need for acute surgical care, a notable example of which is appendicitis. Although performing a laparoscopic appendectomy on Earth is routine for a trained general surgeon, it is far from routine for a non-surgeon working in microgravity where IVs do not drip, drains do not drain, and gaseous anesthetic is out of the question. Because the procedure for laparoscopic appendectomy is so well documented, it was the ideal procedure on which to base a study on how to deconstruct a surgical procedure to examine all actions, skills, equipment, and supplies needed for success by non-surgeons working in an extreme environment. Study Design : Our challenge was to develop a task analysis model robust enough to include 3 performers (in the roles of surgeon, assistant, and anesthesiologist) including each action and instrument or supply item needed in chronological order, while indicating which actions were completed independently and which were done in tandem. We also had to indicate where variations in the actions would be determined by the negative response of the patient (failure mode), and which actions and supply items needed further research to accommodate working in microgravity. We opted to begin with a hierarchical task analysis model (HTA) because the steps in the task are sequential; but we expanded the typical linear presentation of data to a multi-column spread sheet with active links to instructional video clips where needed. Content development was an iterative process beginning with a scoping review of literature to select a baseline task analysis of the procedure. The SAGES 2010 approach was selected as most comprehensive, but logically focused on the surgeon's performance with few references to the assistant or anesthesiologist. Those gaps were filled using content from training materials developed for surgical technicians and nurse anesthetists. The second step was an expert review of the spread sheet to identify gaps and inadequacies. The third step was a minute comparison of spread sheet content to actions and equipment as documented on 2 videotapes of the procedure performed by our team surgeon on otherwise healthy patients. The final review was accomplished by replicating the procedure on 360° video (with narration) using the spread sheet as a guide, then cross checking and correcting the spread sheet to correspond with the 360° video. This test procedure was performed on a lightly preserved, fresh cadaver since working at that very slow, deliberate pace would not be in the best interest of an actual patient. Results: In this study, simulation was actually used to test the expanded HTA rather than to evaluate a learner. The final spread sheet included 178 lines, 13 columns, 13 illustrations, and 4 active links to instructional video clips. Thirteen items or issues were identified as needing further research, 8 action sequences were identified as generalizable skills, and 27 supply or equipment items were identified as multipurpose. Excluding the pharmaceuticals necessary for IV general anesthesia (that research is on-going), we were able to replicate a laparoscopic appendectomy on a fresh cadaver using no more than 30 items. The procedure was done using 3 trocars with very few instrument exchanges through the trocars since the surgical assistant assumed the role of laparoscopic camera operator during the procedure. Conclusion: An expanded HTA of a surgical procedure can produce many useful outcomes including integrated training for all team members, review of instrumentation and supplies and, in our case, identifying areas for adapting to an extreme environment. Using an interdisciplinary team including instructional designers, subject matter experts from medicine and biomedical engineering, and media production enriched the process.